Experience of long-term clinical observation of a patient with a rare type of stomach cancer – lymphoepithelioma-like carcinoma - L. M. Kogoniya; L. E. Gurevich; V. S. Mazurin; E. V. Markarova (Медицинский совет, 2020)
Stomach cancer is one of the most frequently diagnosed cancers. The success of special methods of treatment are still disappointing in this disease, and stomach cancer has historically been considered a tumor refractory to treatment. Therefore, this category of patients, especially in the stage of dissemination, in most cases, palliative therapy is recommended. In recent years, the use of systemic chemotherapy and targeted therapy has led to a significant improvement in the quality of life and survival rates for stomach cancer compared to palliative therapy. However, significant progress in diagnostic methods over the past two decades has made it possible and possible to review approaches to the treatment of many cancer diseases that are refractory to chemotherapy. The last 2 decades, due to improved methods of diagnosis have allowed to revise approaches to the treatment of many refractory to chemotherapy of neoplastic diseases. In particular, the literature describes cases of revision and changes due to pre-existing diagnosis of IHC Research (carcinoid, NEO, stomach cancer, pancreatic cancer). This communication allows to share their own long experience of observation and treatment of a patient with a rare form of stomach cancer – lymphoepithelioma-like carcinoma.